PROTOPRESBYTER ALEXANDER SCHMEMANN ON THE COMMON AND THE PERSONAL IN THE DIVINE LITURGY - V. V. Pechatnov (Концепт: философия, религия, культура, 2017)
The article, for the first time in Russian research, studies the view of protopresbyter Alexander Schmemann on the issue of the relationship between the common and the personal in the Divine liturgy. The investigation showed that Alexander Schmemann, starting from the notion of the liturgy as the common work of the church assembly, and therefore, from the primacy of the common in the liturgy, at the same time acknowledges the existence of the personal, i.e. the importance of the liturgy for each human person. The antinomy between the common and the personal is resolved by Schmemann in accordance with Christ's words in the Gospel: "Whoever desires to save his life will lose it, but whoever loses his life for My sake and the gospel's will save it" (Mk 8:35 and parall.). The investigation is preceded by an introduction to the problematics of Fr. Schmemann's work in the area of liturgy and an indication of his contribution to the study and interpretation of Orthodox worship. In conclusion, the author indicates the sources of Alexander Schmemann's ideas on the problem of the common and the personal in the Divine liturgy and characterizes his own contribution to its solution.